A diagnostic dilemma in breast pathology - benign fibroadenoma with multinucleated stromal giant cells - Tobbia Igdam; Casey Mary; Martin Sean T; Heneghan Helen M; Benani Fadel; Barry Kevin M (BMC, 2008)
Abstract Fibroadenomas are common benign breast tumours that display a characteristic pathological morphology, although several epithelial and stromal variations exist. A very rare histological finding is the presence of multinucleated giant cells throughout the stroma of a benign fibroadenoma. Cells of this type, which are more commonly found incidentally within the interlobular stroma of breast tissue, are benign and should not be mistaken for malignant cells on microscopic examination. Unfortunately a lack of awareness of this pathological entity can lead to diagnostic confusion amongst pathologists resulting in the multinucleate giant cells being mistaken for highly mitotic cells and consequently the fibroadenoma being mistaken for a malignant lesion. This may have serious implications for the subsequent management of the patient. The presence of this unusual cell type in the stroma does not alter the prognosis of otherwise benign lesion. We encountered two such cases at our institution in a six month period recently. We present their histories along with relevant radiological, microscopic and immunohistochemical features, followed by a discussion of this unusual pathological entity.